2007
DOI: 10.1155/2008/863629
|View full text |Cite
|
Sign up to set email alerts
|

Code Tracking Algorithms for Mitigating Multipath Effects in Fading Channels for Satellite-Based Positioning

Abstract: The ever-increasing public interest in location and positioning services has originated a demand for higher performance global navigation satellite systems (GNSSs). In order to achieve this incremental performance, the estimation of line-of-sight (LOS) delay with high accuracy is a prerequisite for all GNSSs. The delay lock loops (DLLs) and their enhanced variants (i.e., feedback code tracking loops) are the structures of choice for the commercial GNSS receivers, but their performance in severe multipath scena… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
58
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 69 publications
(58 citation statements)
references
References 21 publications
0
58
0
Order By: Relevance
“…However, simulation results performed in Irsigler & Eissfeller (2003) showed that ELS is outperformed by HRC with respect to Multipath Error Envelopes (MEEs), for both BPSK and SinBOC(1,1) modulated signals. An Improved ELS (IELS) technique was proposed by the Author in Bhuiyan et al (2008), which introduced two enhancements to the basic ELS approach. The first enhancement was the adaptation of random spacing between the early and the late correlator pairs, while the later one was the utilization of feedforward information in order to determine the most appropriate peak on which the IELS technique should be applied.…”
Section: Early-late-slopementioning
confidence: 99%
See 4 more Smart Citations
“…However, simulation results performed in Irsigler & Eissfeller (2003) showed that ELS is outperformed by HRC with respect to Multipath Error Envelopes (MEEs), for both BPSK and SinBOC(1,1) modulated signals. An Improved ELS (IELS) technique was proposed by the Author in Bhuiyan et al (2008), which introduced two enhancements to the basic ELS approach. The first enhancement was the adaptation of random spacing between the early and the late correlator pairs, while the later one was the utilization of feedforward information in order to determine the most appropriate peak on which the IELS technique should be applied.…”
Section: Early-late-slopementioning
confidence: 99%
“…The first enhancement was the adaptation of random spacing between the early and the late correlator pairs, while the later one was the utilization of feedforward information in order to determine the most appropriate peak on which the IELS technique should be applied. It was shown in Bhuiyan et al (2008) that IELS performed better than nEML only in good C/N 0 for BPSK and SinBOC(1,1) modulated signals in case of short-delay multipath, but still had poorer performance than HRC.…”
Section: Early-late-slopementioning
confidence: 99%
See 3 more Smart Citations